Effects of second-line anti-tuberculosis drugs on the intestinal microbiota of patients with rifampicin-resistant tuberculosis - Wu, Chunli; Yi, Hengzhong; Hu, Yanmei; Luo, Danlin; Tang, Zhigang; Wen, Xinmin; Zhang, Yong; Tang, Mi; Zhang, Lizhi; Wu, Shu; Chen, Mengshi (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To determine the effects of second-line anti-tuberculosis (TB) drugs on the composition and functions of intestinal microbiota in patients with rifampicin-resistant TB (RR-TB). Methods In this cross-sectional study, stool samples and relevant clinical information were collected from patients with RR-TB admitted to the Drug-resistant Specialty Department at Hunan Chest Hospital (Hunan Institute For Tuberculosis Control). The composition and functions of intestinal microbiota were analyzed using metagenomic sequencing and bioinformatics methods. Results Altered structural composition of the intestinal microbiota was found when patients from the control, intensive phase treatment, and continuation phase treatment groups were compared (P<0.05). Second-line anti-TB treatment resulted in a decrease in the relative abundance of species, such as Prevotella copri, compared with control treatment. However, the relative abundance of Escherichia coli, Salmonella enterica, and 11 other conditionally pathogenic species increased significantly in the intensive phase treatment group. Based on differential functional analysis, some metabolism-related functions, such as the biosynthesises of phenylalanine, tyrosine, and tryptophan, were significantly inhibited during second-line anti-TB drug treatment, while other functions, such as phenylalanine metabolism, were significantly promoted during the intensive phase of treatment. Conclusion Second-line anti-TB drug treatment caused changes in the structural composition of the intestinal microbiota in patients with RR-TB. In particular, this treatment induced a significant increase in the relative abundance of 11 conditionally pathogenic species, including Escherichia coli. Functional analysis revealed significantly decreased biosynthesises of phenylalanine, tyrosine, and tryptophan and significantly increased phenylalanine metabolism.